Teams Games Tournament (TGT) Cooperative Learning Model Application to Improve Ecosystem Learning Outcomes for 5th Grade Students - Lianda Sari H, Tetha; Susanti, R. Hariyani; Aramudin, Aramudin (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2023)
Teachers posed an important role in the classroom as a crucial factor in increasing students’ curiosity and attention in learning. However, there are indications that so far, the teacher has been using the same learning model for all lessons, delivering lessons too fast and not systematically, and the lack of guidance in learning. This causes students to have less opportunity to develop their potential. Another impact is that students become passive in learning science so that student learning outcomes and activities decrease. Therefore, this study seeks to improve student learning outcomes through the application of the Times Games Tournament (TGT) cooperative learning model in Ecosystem learning. The research was carried out in two improvement cycles using natural science ecosystem material. The results showed that student learning outcomes increased, in the pre-cycle the students’ scores were â‰¥ 70, 43%, in cycle 1 students’ mastery scores were â‰¥ 70, 54%. Meanwhile, in the second cycle, students’ mastery scores â‰¥ 70 increased to 89%. It can be concluded that the use of the Times Games Tournament (TGT) method can improve learning outcomes for the 5th-grade students in class A, Metta Maitreya Primary School Pekanbaru, Marpoyan Damai District, Pekanbaru City.